Left ventricular morphology and function in endurance-trained female athletes - George, K. P.; Gates, P. E.; Birch, K. M.; Campbell, I. G. (Journal of Sports Sciences, 1999)
In this study,we investigated resting left ventricular dimensions and function in trained female rowers, canoeists and cyclists. In male populations, such athletes have demonstrated the largest left ventricular wall thicknesses and cavity dimensions. Echocardiograms were analysed from 24 athletes (rowers and canoeists, n=12; cyclists, n=12) and 21 age-matched controls to measure left ventricular end-diastolic dimension and volume, and septal (ST) and posterior wall (PWT) thicknesses. Left ventricular mass was calculated from M-mode data. Systolic and diastolic function were calculated from M-mode and Doppler echocardiography, respectively. Height, body mass, body surface area an d fat-free mass were determined anthropometrically. The athletes were well matched with the controls for all anthropometric variables except fat-free mass (rowers and canoeists 49.7 3.6 kg, cyclists 48.0 +/- 3.8 kg, controls 45.0 +/- 5.4 kg; P < 0.05). The left ventricular end-diastolic dimension, mass and volume, and septal and posterior wall thicknesses, were all significantly greater in the athletes than the controls (P < 0.05). These differences persisted (except for left ventricular end-diastolic dimension) even after allometric adjustment for group differences in fat-free mass. Stroke volume was larger (rowers and canoeists 102 +/- 13 ml, cyclists 103 +/0 16 ml, controls 80 +/- 15 ml; P < 0.05) in both groups of athletes but all other functional data were similar between groups. As in male athletes, female rowers, canoeists and cyclists displayed significantly larger left ventricular cavity dimensions and wall thicknesses than controls.